The Transformation of National Identity in Germany: The Role of Political Parties - Hautefeuille, Saya (Université d'Ottawa / University of Ottawa, 2018)
This thesis examines how national identities change and evolve through time. In that sense, it joins other studies that have studied the mechanisms for changes in national identities. While some authors have tended to focus on state structure, institutional changes (i.e. the creation of federal institutions that encourage regional identities) or belief systems, this study argues that political parties play an important role on national identity formulation. Essentially, this study will establish the argument that political parties have an impact on the direction of national identity. Using HI it will illustrate that the institutional framework in which political parties operate affects the direction that they will push national identity towards. Indeed, political actors have a vision for national identity and they will articulate and redefine how national identity is conceptualized but not freely. Rather, how institutions guide actors, preferences and ideas is central to understanding why national identity takes the form and direction that it does. Using the case study of Germany (1949-1969), it will demonstrate that the CDU sought to define German national identity as one based on Christian weltanschauung, integration with the west (westbindung) and social market economy (sozialen Marktwirtschaft) and that with each notion the influence of the Basic Law and previous political institutions could be felt as emphasis would be put on how each concept was related to “freedom”, “individual rights” and “democracy”.
Keywords: NSDAP; CDU; Historical Institutionalism; Political Parties; West Germany